Functional cookies from Spinach flour: A community-based food innovation to improve child nutritional status - Ratnawati T.; Anwar Lubis; Slamet Widodo; Muliani Muliani (Priviet Social Sciences Journal, 2025)
Stunting in early childhood remains a major public health problem that significantly affects growth, cognitive development, and disease susceptibility. One of the key nutritional factors contributing to stunting is iron deficiency, which is closely linked to anemia and metabolic impairment. Spinach   is an affordable and locally available source of iron; however, its utilization in innovative food products for children is still limited. This study aimed to develop spinach flour–based cookies as an alternative supplementary food (PMT) to prevent stunting. An experimental design using a Completely Randomized Design (CRD) with three different formulations of spinach flour was applied. Organoleptic evaluation covering appearance, color, texture, aroma, and taste was carried out by trained panelists, and data were analyzed using the Kruskal–Wallis test, followed by the Mann–Whitney test for significant differences. The nutritional composition was further examined using proximate analysis. The findings showed that the addition of spinach flour improved the iron content and dietary fiber levels while maintaining acceptable sensory qualities. Proximate analysis of the selected formula indicated moisture (3.40%), ash (3.14%), fat (28.88%), protein (6.93%), fiber (37.43%), and carbohydrate (57.65%) contents. These results suggest that spinach flour cookies can be a functional and culturally acceptable snack, providing a promising strategy to address iron deficiency and contribute to stunting-prevention programs. Further clinical and community-based trials are recommended to validate their efficacy in improving the nutritional status of children.